Pneumococcal vaccination coverage in France by general practitioners in adults with a high risk of pneumococcal disease - Aude Kopp; Olivier Mangin; Laurène Gantzer; Béranger Lekens; Guy Simoneau; Manoro Ravelomanantsoa; John Evans; Jean-François Bergmann; Pierre Sellier (Taylor & Francis Group, 2021)
Streptococcus pneumoniae, the main cause of community-acquired pneumonia (CAP), also leads to exacerbations, hospitalizations, and mortality in chronic obstructive pulmonary disease (COPD) and congestive heart failure (CHF). The risk of CAP is increased in patients with diabetes mellitus (DM), and the risk of invasive pneumococcal disease is increased in HIV-infected patients. Pneumococcal vaccination is recommended for these patients in France. The objective was a large survey of pneumococcal vaccination coverage (PVC) by general practitioners (GPs) in these patients in France. Diagnosis and treatment forms were extracted from the database of 2000 GPs. The GPs and population panels were representative of the metropolitan populations. The primary endpoint was the comparison of PVC in the adult patients diagnosed with COPD, CHF, DM, or HIV infection during the study (April 2013-April 2017) and the control (March 2012-March 2013) periods. Of the 17,865 and 4,690 patients identified, 756 (4%) and 267 (6%) were vaccinated, respectively. During the study period, the PVC was significantly higher (35/282, 12%) in HIV-infected patients and lower in patients with DM (95/5994, 2%) than in other patients. Even though French pneumococcal vaccine recommendations in adults were updated in 2013, the PVC did not increase according to the years of the study period and slightly increased according to time after diagnosis. S. pneumoniae is responsible only for some CAP and meningitis, and incomplete protection by vaccine, hesitancy from practitioners and patients, and the moving schedule of vaccination could explain the results. New tools and/or strategies must be implemented to increase PVC in France. Abbreviations: CAP: community-acquired pneumonia; COPD: chronic obstructive pulmonary diseases; CHF: congestive heart failure; DM: diabetes mellitus; IPD: invasive pneumococcal disease; HIV: human immunodeficiency virus; PVC: pneumococcal vaccination coverage; PCV7: 7-valent pneumococcal conjugate vaccine; PCV13: 13-valent pneumococcal conjugate vaccine; PPSV23: 23-valent pneumococcal polysaccharide vaccine; GPs: general practitioners; CLM: Cegedim Logiciels Médicaux; MLM: monLogicielMedical; ICD-10: International Classification of Diseases; CNIL: Commission nationale de l'informatique et des libertés; HPV: human papillomavirus; HBV: hepatitis B virus